The role of metabolic disorders in the development of atherosclerosis: Role of metabolic disorders in atherosclerosis development - Blagov, Alexander V.; Churov, Alexey V.; Golovyuk, Alexander L.; Lee, Arthur A.; Kashtalap, Vasily V.; Sukhorukov, Vasily N.; Orekhov, Alexander N. (Cellular and Molecular Biology, 2024)
Atherosclerosis is a major risk factor for cardiovascular disease (CVD), which is the leading cause of death worldwide. Atherosclerosis is initiated by endothelial activation, followed by a cascade of events (accumulation of lipids, fibrous elements, and calcification) triggering vasoconstriction and activation of inflammatory pathways. This review focuses on the various stages in the development of atherosclerosis, ranging from endothelial dysfunction to plaque rupture. In addition, disorders of lipid, glucose and amino acid metabolism in atherosclerosis are considered here. The key pathological stages of metabolism disruption and their role in atherosclerosis are considered in detail which may be helpful for the more better understanding of atherosclerosis pathogenesis. Finally, some therapeutic approaches aimed at modulating lipid metabolism will also be presented which show the therapeutic targets (enzymes and transport proteins) which modulation can prevent further deterioration of patients symptoms